Spirobranchus sp. Density as a Biological Indicator of Coral Health Under Environmental Stress in Beurawang Waters (SDG 14: Life Below Water) - Afkar; Nadia Aldyza (Postgraduate, University of Mataram, 2026)
This study examines the relationship between the Christmas tree worm (Spirobranchus sp.) and coral health in tropical reef ecosystems. Field observations and statistical analyses were conducted to evaluate worm abundance and its association with coral condition. The results showed a strong association (Phi coefficient = 0.79) between high worm density and degraded coral health. Juvenile Spirobranchus sp. preferentially settle on healthy coral substrates, while adult individuals may contribute to surface abrasion and localized lesions through opercular movement. Exposed worm tubes can facilitate turf algae colonization, inhibiting coral recovery. Environmental parameters, including temperature, pH, salinity, visibility, and current velocity, influence coral condition and worm distribution. Elevated and localized temperature anomalies and reduced water flow were associated with increased coral stress and algal growth. These findings indicate that Spirobranchus sp. may contribute to coral degradation under high population density. This study supports Sustainable Development Goal 14 (Life Below Water) by highlighting the potential of Spirobranchus sp. density as a practical indicator for coral reef monitoring and conservation.